2011
DOI: 10.1308/003588410x12771863936765
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative patient education reduces length of stay after knee joint arthroplasty

Abstract: The results suggest that pre-operative education is a safe and effective method of reducing length of stay for knee arthroplasty patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(87 citation statements)
references
References 23 publications
(35 reference statements)
6
73
1
6
Order By: Relevance
“…However, Mahomed et al [16] reported a readmission rate of only 0.9% in a similar Medicare cohort. Huddleston et al suggested that their higher readmission rate might be the result of earlier discharge after TKA, although this explanation remains controversial [4,9,22]. The low readmission rate reported by Mahomed et al may also be the result of how they defined readmission, which was limited to a specific list of diagnoses rather than a true all-cause readmission rate.…”
Section: Discussionmentioning
confidence: 98%
“…However, Mahomed et al [16] reported a readmission rate of only 0.9% in a similar Medicare cohort. Huddleston et al suggested that their higher readmission rate might be the result of earlier discharge after TKA, although this explanation remains controversial [4,9,22]. The low readmission rate reported by Mahomed et al may also be the result of how they defined readmission, which was limited to a specific list of diagnoses rather than a true all-cause readmission rate.…”
Section: Discussionmentioning
confidence: 98%
“…Wang (2002) have found that the introduction of an education programme resulted in improved quality of gait and endurance at 6 months [17]. There was also reduction in hospital length of stay when combined with rehearsal of postoperative exercises resulting in cost savings, which has been supported by other studies in current literature [16]- [18]. Furthermore, the assessment of patient's home and family environment by nurses and physiotherapists before surgery increased patient satisfaction and lightened postoperative management [10].…”
Section: Educationmentioning
confidence: 80%
“…A more recent review linked preoperative education to improved patient outcomes including lower hospital length of stay, higher home discharge, lower readmission and improved costs [2]. Additionally, other recent evidence that was not included in the Cochrane review has demonstrated that the provision of preoperative education is linked to a reduction in hospital length of stay [4][5][6][7].…”
Section: Main Text Backgroundmentioning
confidence: 99%